THE CARING BEHAVIOR OF VOLUNTARY NURSES TO THE CLIENT IN PADANGSIDIMPUAN GENERAL HOSPITAL - Hotma Royani Siregar; Adi Antoni (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2016)
Voluntary nurses is the nurses who provide health care voluntarily without expecting any fee. Caring behavior of voluntary nurses is the skill of voluntary nurses giving attention, empaty,and helping clients to fullfil their daily needs as long as voluntary nurses giving nursing care in hospital. The objective of the research was to explore deeply caring behavior of voluntary nurses to the client in Padangsidimpuan General Hospital. The research used phenomenological design. The data were gathered by conducting in-depth interviews. Purposive sampling technique was used to select the participants who had met the criteria. They consisted of 6 voluntary nursesin Padangsidimpuan General Hospital. The result of the interviews was recorded and analyzed by using content analysis. The result of the research showed that there were 4 themes which reflected the research phenomena. They were Voluntary Nurses care to the clients, Voluntary nurses doing holistic nursing care, Voluntary nurses respect clients, and The effects of caring behavior of voluntary nurses. It is recommended that the Voluntary nerses alwaysapply caring behavior to the client even though without recieve any fee. Keywords: Behavior, Caring, Voluntary Nurses, Client